2021
DOI: 10.3390/foods10102458
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Coffee and Tea Consumption during the COVID-19 Pandemic

Abstract: Over the last two years, many countries have enforced confinement to limit both the spread of COVID-19 and the demand for medical care. Confinement has resulted in a disruption of work routines, boredom, depression, and changes in eating habits, among them consumption of coffee and tea. Following six databases, we examined articles tracking consumption of these beverages. Out of 472 articles, including 23 beverage entries, 13 matched our criteria. While no clear trend in coffee consumption during the coronavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 32 publications
1
24
0
3
Order By: Relevance
“…On the other hand, no changes in coffee consumption were observed, whereas a statistically significant increase in tea consumption was noted, which is in line with the review by Castellana et al (2021). As the authors emphasize, tea is associated with relaxation, concentration, and being at home [59]. The increase in the consumption of sweets was not statistically significant.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, no changes in coffee consumption were observed, whereas a statistically significant increase in tea consumption was noted, which is in line with the review by Castellana et al (2021). As the authors emphasize, tea is associated with relaxation, concentration, and being at home [59]. The increase in the consumption of sweets was not statistically significant.…”
Section: Discussionsupporting
confidence: 81%
“…The 2021 review shows the overall increase in alcohol consumption during the COVID-19 pandemic [58]. On the other hand, no changes in coffee consumption were observed, whereas a statistically significant increase in tea consumption was noted, which is in line with the review by Castellana et al (2021). As the authors emphasize, tea is associated with relaxation, concentration, and being at home [59].…”
Section: Discussionmentioning
confidence: 61%
“…As caffeine might be the most consumed psycho-stimulant around the world, and due to its likely complex effect on anxiety, further research in this field is needed. Moreover, results from recent studies suggested an increase in coffee, tea, and energy drink consumption during the COVID-19 pandemic [ 18 , 19 , 20 ]; as these beverages are the principal caffeine sources, caffeine intake might have also increased, and have become an additional risk factor for anxiety during this period and possibly beyond. The reported increased anxiety disorder prevalence during the COVID-19 pandemic in 2020–2021 underscores the urgency to strengthen mental illness prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Precisely due to this positive effect on improving mood, it is easy to understand why their consumption intensified during the SARS-CoV-2 lockdown when social isolation and estrangement from relatives were already causing psychological distress, stress, and bad mood. Along this same line of thinking, nerve drinks, such as coffee and tea, were found to have an increased consumption during lockdowns [ 10 ]. However, the exceptional circumstances of the shutdown provided a positive opportunity for some people to spend more time cooking at home; though that attitude improved culinary approaches, it most often led to increased cooking of carbohydrate-dense foods, such as pizza, bread, and baked goods [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…These latter are part of the so-called comfort foods—in other words, foods whose consumption provides consolation or a feeling of wellbeing due to their palatability and sweet taste releasing serotonin. For example, when considering beverages, there was increased consumption of coffee and tea during the pandemic due to their mood-modulating capacity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%